The 1, 6, 7, 12‐Tetraazaperylene Bridging Ligand as an Electron Reservoir and Its Disulfonato Derivative as Redox Mediator in an Enzyme–Electrode Process. Issue 62 (4th September 2017) - Brietzke, Thomas; Dietz, Thomas; Kelling, Alexandra; Schilde, Uwe; Bois, Julianae; Kelm, Harald; Reh, Manuel; Schmitz, Markus; Körzdörfer, Thomas; Leimkühler, Silke; Wollenberger, Ulla; Krüger, Hans‐Jörg; et al.
Abstract: The homodinuclear ruthenium(II) complex [{Ru(l ‐N4 Me2 )}2 (μ‐tape)](PF6 )4 {[1 ](PF6 )4 } (l ‐N4 Me2 = N, N ′‐dimethyl‐2, 11‐diaza[3.3](2, 6)‐pyridinophane, tape=1, 6, 7, 12‐tetraazaperylene) can store one or two electrons in the energetically low‐lying π* orbital of the bridging ligand tape. The corresponding singly and doubly reduced complexes [{Ru(l ‐N4 Me2 )}2 (μ‐tape .− )](PF6 )3 {[2 ](PF6 )3 } and [{Ru(l ‐N4 Me2 )}2 (μ‐tape 2− )](PF6 )2 {[3 ](PF6 )2 }, respectively, were electrochemically generated, successfully isolated and fully characterized by single‐crystal X‐ray crystallography, spectroscopic methods and magnetic susceptibility measurements. The singly reduced complex [2 ](PF6 )3 contains the π‐radical tape .− and the doubly reduced [3 ](PF6 )2 the diamagnetic dianion tape 2− as bridging ligand, respectively. Nucleophilic aromatic substitution at the bridging tape in [1 ] 4+ by two sulfite units gave the complex [{Ru(l ‐N4 Me2 )}2 {μ‐tape‐(SO3 )2 }] 2+ ([4 ] 2+ ). Complex dication [4 ] 2+ was exploited as a redox mediator between an anaerobic homogenous reaction solution of an enzyme system (sulfite/sulfite oxidase) and the electrode via participation of the low‐energy π*‐orbital of the disulfonato‐substituted bridging ligand tape–(SO3 )2 2− ( E red1 =−0.1 V versus Ag/AgCl/1 m KCl in water). Abstract : Full of negativity : The redox‐active bridging ligand 1, 6, 7, 12‐tetraazaperylene (tape) contained in a dinuclear ruthenium(II) complex can store up to two electrons, demonstrated by the isolation and characterization of the singly and doubly reduced dinuclear complexes. The high π‐accepting potential of the tetraazaperylene bridge can be increased further by introducing two sulfonato groups. The corresponding complex works as a redox mediator in a voltammetric enzyme–electrode system.